1988
DOI: 10.1007/bf00305011
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the type II cell or its precursor before week 20 of human gestation, using antibodies against surfactant-associated proteins

Abstract: The present study was performed to find out whether the type II alveolar epithelial cell or its precursor (an approximately cuboidal cell lacking multilamellar bodies) is present before the twentieth week of human gestation. For this purpose we used an antibody, SALS-Hu(E), which recognizes the human type II cell on the basis of surfactant-associated proteins. Application of SALS-HuE (by indirect immunofluorescence) to acetone-fixed frozen sections of fetal lung tissue gave a distinct staining of the cuboidal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…These studies provide some information on cell properties, but not on cellular distribution patterns along the bronchioles, and generally consider both the columnar and the cuboid cell types present in the lining as bronchial epithelial cells. This classic view on the epithelial composition is not supported, however, by our developmental studies in humans (Otto-Verberne et al, 1988) and a nonhuman primate, the rhesus monkey (Ten Have-Opbroek and Plopper, 1989).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…These studies provide some information on cell properties, but not on cellular distribution patterns along the bronchioles, and generally consider both the columnar and the cuboid cell types present in the lining as bronchial epithelial cells. This classic view on the epithelial composition is not supported, however, by our developmental studies in humans (Otto-Verberne et al, 1988) and a nonhuman primate, the rhesus monkey (Ten Have-Opbroek and Plopper, 1989).…”
mentioning
confidence: 85%
“…The specificity of these antibodies, called specific antilavage serum, human (SALS-Hu), was assessed by Western blot analysis and immunohistochemistry (Otto-Verberne et al, 1988). These studies also showed the type I1 cell specificity of SALS-Hu in both developing and adult human lungs (Otto-Verberne et al, 1988). Blood samples taken before immunization were used as control (preimmunization serum, PSI.…”
Section: Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…26 They have been detected in the mouse from day 14 26 on, in the rat from day 16, 57 and in human lungs from week 11-12. 58 Further differentiation of the type II cells into type I cells starts in the human from gestational week 16 onward. 58 Alveolar type II cells are the only cells in the lung responsible for the production, storage, and secretion of pulmonary surfactant. Surfactant is composed of 85 59,60 The composition of surfactant phospholipids and proteins, as well as their functions, have been reviewed repeatedly.…”
Section: Development Of the Surfactant Systemmentioning
confidence: 99%
“…Around 16 weeks a.c., there is also a third stage in the alveolar epithelial cell differentiation, mainly in those areas of the acinus that are close to capillaries. This is a 'flatter' cell type, ranging in shape from cuboidal to squamous, that represents an intermediate stage in the differentiation of prospective cuboidal type II cells into prospective squamous type I cells (Ten Have-Opbroek, 1979Otto-Verberne and Ten Have-Opbroek, 1987;Otto-Verberne et al, 1988;Ten Have-Opbroek and Plopper, 1992;Brandsma et al, 1993Brandsma et al, , 1994. As a consequence of this cell 'flattening,' the acinar tubules start to transform into derivative structures, namely prospective alveolar ducts and sacs (canalicular period of lung development).…”
mentioning
confidence: 99%